Antivirulence activity of azithromycin in Pseudomonas aeruginosa - Imperi, Francesco; Leoni, Livia; Visca, Paolo (Frontiers in Microbiology, 2014)
Antibiotics represent our bulwark to combat bacterial infections, but the spread of antibiotic resistance compromises their clinical efficacy. Alternatives to conventional antibiotics are urgently needed in order to complement the existing antibacterial arsenal. The macrolide antibiotic azithromycin (AZM) provides a paradigmatic example of an “unconventional” antibacterial drug. Besides its growth-inhibiting activity, AZM displays potent anti-inflammatory properties, as well as antivirulence activity on some intrinsically resistant bacteria, such as Pseudomonas aeruginosa. In this bacterium, the antivirulence activity of AZM mainly relies on its ability to interact with the ribosome, resulting in direct and/or indirect repression of specific subsets of genes involved in virulence, quorum sensing, biofilm formation and intrinsic antibiotic resistance. Both clinical experience and clinical trials have shown the efficacy of AZM in the treatment of chronic pulmonary infections caused by P. aeruginosa. The aim of this review is to combine results from laboratory studies with evidence from clinical trials in order to unify the information on the in vivo mode of action of AZM in P. aeruginosa infection.